Mean Atomic Number Quantitative Assessment in Backscattered Electron Imaging - Sanchez, Eloy Sebastian (2012)
A method for obtaining quantitative mean atomic number images in a scanning electron microscope for different kinds of samples has been developed. The backscattered electron signal is monotonically increasing with the mean atomic number Z, and accordingly Z can be given as a function of the image gray levels. From results obtained from Monte Carlo simulations, an exponential function is fitted to convert the backscattered registered gray levels into a Z image map. Once this fitting was performed, the reproducibility of the Z determination was checked through the acquisition of backscattered electron images from metal and mineral standards. The developed method can be applied to any unknown sample, always controlling the experimental conditions, as shown here for a thin section of a rock in which several unknown mineral phases are present; the results obtained herein are compared to quantitative assessments performed with X-ray spectra from each mineral phase.